Ubc13 and COOH terminus of Hsp70-interacting protein (CHIP) are required for growth hormone receptor endocytosis - Slotman, Johan A; da Silva Almeida, Ana C; Hassink, Gerco C; van de Ven, Robert H A; van Kerkhof, Peter; Kuiken, Hendrik J; Strous, Ger J (The Journal of biological chemistry, 2012)
Growth hormone receptor (GHR) endocytosis is a highly regulated process that depends on the binding and activity of the multimeric ubiquitin ligase, SCF(βTrCP) (Skp Cullin F-box). Despite a specific interaction between β-transducin repeat-containing protein (βTrCP) and the GHR, and a strict requirement for ubiquitination activity, the receptor is not an obligatory target for SCF(βTrCP)-directed Lys(48) polyubiquitination. We now show that also Lys(63)-linked ubiquitin chain formation is required for GHR endocytosis. We identified both the ubiquitin-conjugating enzyme Ubc13 and the ubiquitin ligase COOH terminus of Hsp70 interacting protein (CHIP) as being connected to this process. Ubc13 activity and its interaction with CHIP precede endocytosis of GHR. In addition to βTrCP, CHIP interacts specifically with the cytosolic tails of the dimeric GHR, identifying both Ubc13 and CHIP as novel factors in the regulation of cell surface availability of GHR.